DETERMINANT FACTORS OF TOOTH PULP CARIES IN ROWOSARI, SEMARANG, INDONESIA - Latifah, Rose Asni; Subekti, Ani; Suwarsono, Suwarsono; Sutomo, Bambang (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Tooth pulp caries is commonly found in community Rowosari, Semarang, Indonesia based on the patient visit at the public health centre. The process of the pulp caries occur because of clinical factors including the interaction among host, agent, environment, and time. Non-clinical factors including environment, attitude, health care and heredity. Aims: This study aims to determine the factors that cause pulp caries in community Rowosari, Semarang, Indonesia year 2016. Methods: It is descriptive quantitative research with case control study design. The sampling technique used nonprobability sampling by purposive sampling with 74 samples which consist of case group is the community which has pulp caries and control group is that havent pulp caries. Data collection techniques of clinical factors by direct examination, while nonclinical factors using questionnaires. Analysis of the data used is the Odds Ratio. Results: In the case group showed the highest odds ratio value on clinical factors are plaque index (OR = 4.524), which means that people with high plaque index have 4.524 times greater risk than the well index plaque. In non-clinical factors Odds Ratio is the highest value of action (OR = 1.949), which means people with bad actions have 1.949 times greater risk than those with good action. Conclusion: There are several caused factor of pulp caries. Biggest caused by the clinical factors is the plaque index, while biggest caused nonclinical factors are action. It is suggested that the community has to know and apply good dental health care in daily activities to reduce dental plaque.Â